Health on equal terms? - Västra Götaland, 2006 - Health on equal terms, Västra Götaland - 2006 - Public Health Agency of Sweden (Region Västra Götaland, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004.
The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2006, Region Västra Götaland ordered an additional sample for Västra Götaland County.

The additional sample in 2006 included all individuals aged 16-84 years living in Västra Götaland County. A total of 21,075 individuals answered the questionnaire, representing a response rate of 59,1 percent.

The questionnaire was printed in two versions. Addition to the national public health questionnaire, a similar questionnaire was conducted including the EQ-5D instrument. The questionnaire with the EQ-5D instrument was sent to the additional sample in Västra Götaland County. The national questionnaire consisted a total of 134 questions and the questionnaire including the EQ-5D instrument consisted a total of 136 questions. Both questionnaires covered issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaires, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Västra Götaland County was to investigate the health in the population in Västra Götaland County.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningarna har Västra Götalandsregionen beställt ett tilläggsurval för Västra Götalands län.

Tilläggsurvalet för 2006 års undersökning inkluderade samtliga invånare 16-84 år i Västra Götalands län. Frågeformuläret besvarades av totalt 21 075 individer inom Västra Götalands län, vilket motsvarade en svarsfrekvens på 59,1 procent.

Det trycktes två olika versioner av frågeblanketten, dels den nationella frågeblanketten och dels en variant som innehöll nästan alla frågor i den nationella blanketten samt frågeinstrumentet EQ5D. Västra Götalands regionen valde att deras tilläggsurval skulle få EQ5D-blanketten. Den nationella frågeblanketten bestod av 77 numrerade frågor varav flera hade delfrågor, vilket genererade totalt 134 frågor. EQ5D-blanketten bestod av 75 numrerade frågor varav flera hade delfrågor, vilket genererade totalt 136 frågor. Frågorna handlade bl.a. om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Förutom variabler som samlats in via frågeblanketten har ett antal registervariabler hämtats från SCB:s Registret över totalbefolkningen (RTB), utbildningsregistret, inkomst- och taxeringsregistret samt Geodatabasen.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Västra Götalands län var att ta reda på hur befolkningen i Västra Götalands län mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2006 - Hälsa på lika villkor, Västra Götaland - 2006
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Job Satisfaction; Arbetstillfredsställelse; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Hypersensitivity; Överkänslighet